基于本征时间尺度分解算法的齿轮箱故障诊断 - 林近山 (Jixie chuandong)
Aiming at the shortcomings of current signal processing methods for fault diagnosis of gear box,the intrinsic time-scale decomposition（ITD） algorithm is used to diagnose the faults of gear box.To begin with,the ITD method is presented,then the ITD method is applied to the fault diagnosis of a defective gearbox and successfully obtained the correct conclusion.Finally,the ITD method is compared with the EMD method.The results show that,the ITD method has a clear advantage over the EMD method in increasing the computation speed and constraining the end point effect.A new method for the fault diagnosis of gear box is provided.